Trends of serum 25(OH) vitamin D and association with cardiovascular disease and all-cause mortality: from NHANES survey cycles 2001–2018 - Hu, Changlun; Yang, Mei (Frontiers in Nutrition, 2024)
The focus of this survey is on survey data for adults aged 20 and above, covering nine survey cycles from 2001 to 2018. Additionally, the present study explored delved into the correlation between vitamin D concentrations and both cardiovascular disease (CVD) and all-cause mortality.The objectives of this study were to evaluate included evaluating the trend of changes in the serum 25(OH)D concentration changes in US adults during the survey period, the prevalence of vitamin D deficiency, and the current status of vitamin D dietary intake and supplementation.In-home health interviews were performed using meticulously designed questionnaires that gathered information on demographic details, socioeconomic conditions, dietary patterns, and overall health status. Health assessments were conducted in specially designed mobile centers[https://wwwn.cdc.gov/nchs/nhanes/tutorials/default.aspx].